Identifying the predictors of first-pass effect and its influence on clinical outcome in the setting of endovascular thrombectomy for acute ischemic stroke: Results from a multicentric prospective registry. Issue 1 (January 2021) - Di Maria, Federico; Kyheng, Maéva; Consoli, Arturo; Desilles, Jean-Philippe; Gory, Benjamin; Richard, Sébastien; Rodesch, Georges; Labreuche, Julien; Girot, Jean-Baptiste; Dargazanli, Cyril; Marnat, Gaultier; Lapergue, Bertrand; et al.
Background: The first-pass effect, defined as a complete or near-complete recanalization after one pass (first-pass effect) of a mechanical thrombectomy device, has been related to better clinical outcome than good recanalization after more than one pass in acute ischemic stroke. We searched for predictors of first-pass effect by analyzing the results within a large prospective multicentric registry. Methods: We included patients treated by mechanical thrombectomy for isolated anterior intracranial occlusions. A multi-variate logistic regression analysis was carried out to search for predictors of first-pass effect. We also analyzed the percentage of patients with 90-day modified Rankin Scale score 0 to 2, excellent outcome (90-day modified Rankin Scale 0 to 1), 24-h NIHSS change, and 90-day all-cause mortality. Results: Among the 1832 patients included, clinical outcome at 90 days was significantly better in first-pass effect patients (50.6% vs. 38.9% in patients without first-pass effect), with a center-adjusted OR associated with first-pass effect of 1.74 (95%CI, 1.24 to 1.77). Older age, a lower systolic blood pressure, an MCA-M1 occlusion, higher DWI-ASPECTS at admission, mechanical thrombectomy under local anesthesia, and combined first-line device strategy were independent predictors of first-pass effect. Conclusions: In this study, a strategy combining thrombectomy and thrombo-aspiration was more effective than other strategies in achieving first-pass effect. In addition, we confirm that clinical outcome was better in patients with first-pass effect compared to non-first-pass effect patients.